2015
DOI: 10.1007/s13277-015-4104-9
|View full text |Cite
|
Sign up to set email alerts
|

Antidiabetic exendin-4 activates apoptotic pathway and inhibits growth of breast cancer cells

Abstract: Exendin-4 is a GLP-1 analog used for the treatment of type 2 diabetes mellitus in its synthetic form. As women with diabetes have higher breast cancer incidence and mortality, we examined the effect of the incretin drug exendin-4 on breast cancer cells. The aim of the study is to investigate anticancer mechanism of exendin-4 in MCF-7 breast cancer cells. Cytotoxic effects of exendin-4 were determined by XTT assay. IC50 dose in MCF-7 cells were detected as 5 μM at 48th hour. Gene messenger RNA (mRNA) expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 28 publications
3
12
0
Order By: Relevance
“…Breast cancer is among the most common types of malignant tumors that affect women, according to statistics from developed countries in North America and Europe ( 30 ). Several studies have reported that breast cancer incidence and mortality risk are closely associated with metabolic disease ( 31 33 ). The present study reported that liraglutide, which is widely employed for hypoglycemic treatment, also exhibited an inhibitory effect on the proliferation of MCF-7 cells and promoted apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Breast cancer is among the most common types of malignant tumors that affect women, according to statistics from developed countries in North America and Europe ( 30 ). Several studies have reported that breast cancer incidence and mortality risk are closely associated with metabolic disease ( 31 33 ). The present study reported that liraglutide, which is widely employed for hypoglycemic treatment, also exhibited an inhibitory effect on the proliferation of MCF-7 cells and promoted apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, the scarce in vitro data limit our understanding of the role of incretins and cancer. Although the mechanisms of action of GLP-1 analogs are yet to be elucidated, GLP-1 analogs have been shown to influence cancer cells by altering proliferation, apoptosis, ECM remodeling and the response to chemotherapy ( 17 , 18 , 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…The role of GLP-1 analogs on cancer cell growth and invasion both in vitro and in vivo is yet to be elucidated. Incretins have shown to inhibit growth and enhance apoptosis of cancer cells through inhibition of the PI3K/Akt pathway for some cell lines of breast ( 17 ), colon cancer ( 18 ) and ovarian cancer ( 19 ). Thus, understating of the role of GLP-1 analogs has important clinical implication in the design of novel anti-cancer therapies emphasizing the potential benefits of combining both incretins with chemotherapy-cytostatic drugs.…”
Section: Introductionmentioning
confidence: 99%
“…Several evidences obtained from in vitro studies indicate that GLP-1 agonists can exert growth inhibition effects on breast cancer lines [12,13,16]. However, these investigations were mostly done by either exenatide (exendine-4), the first widely used GLP-1 agonist, or on the MCF-7 cell line, which represents a poorly aggressive and non-invasive phenotype [17] of breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Incretins have been shown to enhance cell proliferation in several tissues including pancreas, central nervous and gastrointestinal systems [11] and as a result increased risk of cancer development can be assumed. On the other hand, GLP-1 agonists have been found to be toxic for breast cancer cells [12,13]. In most of these studies the oldest FDA approved GLP-1 agonist, exenatide, has been used.…”
Section: Introductionmentioning
confidence: 99%